Pre-Activation Negativity (PrAN) in Brain Potentials to Unfolding Words - Söderström, Pelle; Horne, Merle; Frid, Johan; Roll, Mikael (Frontiers in Human Neuroscience, 2016)
We describe an ERP effect termed the ‘pre-activation negativity’ (PrAN), which is proposed to index the degree of pre-activation of upcoming word-internal morphemes in speech processing. Using lexical competition measures based on word-initial speech fragments (WIFs), as well as statistical analyses of ERP data from three experiments, it is shown that the PrAN is sensitive to lexical competition and that it reflects the degree of predictive certainty: the negativity is larger when there are fewer upcoming lexical competitors.